PENGARUH MANAJEMEN PENGETAHUAN, BUDAYA ORGANISASI DAN KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI - Lucia Evianti Patulak; Buyung Sarita; Wahyuniati Hamid (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
The objectives of the study are : (1) The effect of knowledge management, organizational culture  and work involvement simultaneously have effect on Employees performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province; (2) the effect of partial  knowledge management on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province; (3) The effect of partial  organizational culture on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province;  (4) The effect of partial  Work involvement on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province. The research design used was quantitative research. The population of the study were all employees who worked at the Secretariat Office of the DPRD Southeast Sulawesi Province. The analysis used is quantitative analysis using Multiple Linear Regression Analysis. The results of this study found that: (1) knowledge management, organizational culture and work involvement simultaneously have positif and signifikant effect on employee performance at the Secretariat Office of the DPRD Southeast Sulawesi Province; (2) Knowledge management has positip and significant effects on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province; (3) Organizational culture has has poositip and significant on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province;  (4) Work involvement has positif and significant on Employees Performance at the Secretariat Office of the DPRD of Southeast Sulawesi Province